How close is Iraq to getting the bomb?. - Broder, J.
How close is Iraq to developing a nuclear weapon? Evidence of an imminent threat is underwhelming but still unsettling. US President George W, Bush, supported by some independent strategic experts, says it could be a matter of months. Others say international arms inspectors effectively destroyed Saddam Hussein's nuclear program in the aftermath of the 1991 Persian Gulf War and that it would take him several years of unconstrained work to produce an atomic bomb-an unlikely prospect given the tough new arms inspection regime adopted by the United Nations Security Council and the threat of a US-led invasion. Coloring all these estimates is a palette of war fever, proliferation fears, and the murky politics of arms inspections. The short answer is that nobody knows how close the secretive Saddam is to having his long-sought atomic bomb. There is simply no way to tell, but that hasn't stopped the speculation about what is surely the most pressing issue in international affairs, if only because the Bush administration has stated it will take unilateral military action, if necessary to stop Saddam.
Keywords: Iraq; US-led invasion threat; Arms inspection regime; Atomic bomb; International arms inspectors; Nuclear proliferation; Nuclear weapon development; Politics